Breakpoint characterization of the der(19)t(11;19)(q13;p13) in the ovarian cancer cell line SKOV‐31. Issue 5 (30th January 2013) - Onkes, Wiebke; Fredrik, Regina; Micci, Francesca; Schönbeck, Benjamin J; Martin‐Subero, Jose I; Ullmann, Reinhard; Hilpert, Felix; Bräutigam, Karen; Janssen, Ottmar; Maass, Nicolai; Siebert, Reiner; Heim, Sverre; et al.
Abstract About 20% of ovarian carcinomas show alterations of 19p13 and/or 19q13 in the form of added extra material whose origin often is from chromosome 11. Based on earlier spectral karyotype analysis of the ovarian cancer cell line SKOV‐3, which shows an unbalanced translocation der(19)t(11;19), the aim of this study was to determine the precise breakpoints of that derivative chromosome. After rough delimitation of the breakpoints of microdissected derivative chromosomes by array analysis, we designed a matrix of primers spanning 11q13.2 and 19p13.2 detecting multiple amplicons on genomic and cDNA. Sequencing the amplicons, accurate localization of both breakpoints on both chromosomes was possible and we found that exon 14 of HOOK2 from chromosome 19 and exon 2 of ACTN3 from chromosome 11 were fused in the derivative chromosome. The breakpoint in the HOOK2 gene was in an intrinsic triplet of nucleic acids leading to a shift in the ACTN3 reading frame in the derivative chromosome. This frameshift alteration should give rise to an early stop codon causing a loss of function of ACTN3. Signals in two‐dimensional Western blotting exactly match to calculated molecular mass and the isoelectric point of the fusion protein. © 2013 Wiley Periodicals, Inc.